Utilizing magnetic signatures to investigate geologic strength using computer software in parts of Ibadan, Nigeria - Kiani, Innocent; Chikweri, Irene Ndidi; Raphael, Okosiemiema (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
In light of earthquake activity and its consequences for civil engineering construction, this study explores the subsurface stability of Ibadan, Nigeria. The study uses high-resolution aeromagnetic data to perform a thorough structural analysis, with an emphasis on the identification of fault systems and their possible relationship to seismic activity. It does this by using Geosoft Oasis Montaj 6.4.2 data processing and analysis software. Numerous crystalline rocks, such as the gneiss-migmatite complex, quartz, pegmatite, amphibolites, xenoliths, and aplites, compose the geological framework of Ibadan. The study area is 55 by 55 km in size and is situated in the southwest of Nigeria. Its latitudes are 3° 30' to 4° 00' east and 7° 00' to 7° 30' north. The total magnetic intensity (TMI) data that Fugro Airborne Survey Limited gathered between 2003 and 2009 served as the foundation for the aeromagnetic study. The collected data was carefully processed, going through stages like leveling, gridding, correction for the International Geomagnetic Reference Field, and de-cultivation. To extract meaningful information, reduction techniques were used, such as the Total Horizontal Derivative (THDR) and the Reduction to Magnetic Equator (RTE). Based on magnetic lineament analysis, the results show three prominent fault trends: ENE-WSW, NW-SE, and NE-SW. The possible seismic significance of these fault trends is highlighted by the structural analysis, which includes a superimposition of magnetic faults on the updated geological map. There is a correlation between the observed tremors in Ogun State and Ibadan and historical earthquake events, specifically the NE-SW and ENE-WSW fault sets. Insights from this study are very helpful for Ibadan's construction planning and earthquake risk assessment. The detected fault systems emphasize how crucial it is to take seismic hazards into account when planning urban development projects, particularly the NE-SW and ENE-WSW trends. A solid basis for well-informed decision-making is provided by the software-enabled analysis, which improves the area's earthquake readiness and helps to build resilient infrastructure.